Effects of Off-season Nutritional Education on Dietary Improvement in Female Rhythmic Gymnasts during Weight Reduction Periods - Kisara, Kumiko; Hashizume, Misuzu; Hida, Azumi; Kokubo, Yuki; Yokoyama, Yuri; Sunami, Ayaka; Yamada, Mieko; Yoshizaki, Takahiro; Kawano, Yukari; Ishizaki, Sakuko; Tada, Yuki (Eiyōgaku zasshi, 2013)
Objective: The present study aimed to investigate whether off-season nutritional education for female rhythmic gymnasts during their weight reduction periods might help prevent decreased protein intake and anemia. Methods: Fourteen female rhythmic gymnasts participated in this study, which was conducted from Jun 2009 (before weight reduction) to Aug 2010 (after weight reduction). Nutritional education was provided during the off-season period (Feb-Apr 2010) and included lectures as well as classes on shopping, cooking, and menu planning. Physical characteristics and dietary intake were assessed four times in total before (Jun) and after (Aug) the weight reduction periods in both 2009 and 2010. Results: No significant differences in physical characteristics, hematological values, and dietary intake were observed between 2009 and 2010 except in terms of body weight, body mass index, lean body weight, and red blood cell counts. There was a significant decrease in the protein-energy ratio and intake of beans and eggs in Aug 2009, and body fat in Aug 2010. In addition, egg intake was significantly higher in Aug 2010 than in Jun 2010. These results show that, compared to 2009, body fat changes during the weight reduction periods significantly decreased in 2010, whereas changes in hematocrit, intake of protein, beans and eggs, and protein-energy ratio significantly increased in 2010. Conclusions: Off-season nutritional education for female rhythmic gymnasts during their weight reduction periods may help prevent decreased protein intake, but it does not seem to affect the iron status parameters, with the exception of the hematocrit level.